Comprehensive Analysis of YTHDF1 Immune Infiltrates and ceRNA in Human Esophageal Carcinoma - Liu, Xu-Sheng; Kui, Xue-Yan; Gao, Yan; Chen, Xue-Qin; Zeng, Jing; Liu, Xiao-Yu; Zhang, Yu; Zhang, Yao-Hua; Pei, Zhi-Jun (Frontiers in Genetics, 2022)
Background: YTHDF1 is highly expressed in multiple tumors and affects tumor progression. However, few comprehensive studies on the analysis of YTHDF1 in esophageal cancer. Methods: We analyzed YTHDF1 expression in pan-cancer by comparing both the GEPIA and TCGA cohorts, and further verified the differences in YTHDF1 expression between ESCA and normal group by the GEO ESCA cohort and in vitro experiments. The correlation of YTHDF1 expression and the clinical characteristics of ESCA patients was analyzed using TCGA ESCA clinical data. The GO and KEGG enrichment analyses of the YTHDF1 co-expressed genes were completed by bioinformatics analysis, and the GGI and PPI were constructed for the YTHDF1, respectively. The relationship between YTHDF1 expression and the infiltration of ESCA immune cells was analyzed by using the TIMER database and the TCGA ESCA cohort. The relationships between YTHDF1 expression levels and glycolysis and ferroptosis related genes were analyzed using the TCGA and GEPIA ESCA cohorts. Finally, the ceRNA network that may be involved in YTHDF1 in ESCA was predicted and constructed through a variety of databases. Results: YTHDF1 was overexpressed in various cancers, and in vitro experiments confirmed that YTHDF1 expression was higher in ESCA samples than in normal samples. The expression of YTHDF1 has some accuracy in predicting the tumor outcome. Expression of YTHDF1 was significantly associated with multiple clinical features in ESCA patients. GO and KEGG enrichment analyses indicated that YTHDF1 co-expressed genes involved multiple biological functions. There is a potential association between YTHDF1 expression and multiple immune cell infiltration, glycolysis and ferroptosis related genes in ESCA. YTHDF1 may be involved in multiple ceRNA regulatory networks in ESCA, including PAXIP1-AS1/has-miR-376c-3p/YTHDF1 axis, THUMPD3-AS1/hsa-miR-655-3p/YTHDF1 axis and SNHG20/hsa-miR-655-3p/YTHDF1 axis, respectively. Conclusions: YTHDF1 can serve as a biomarker of ESCA, related to the immune cell infiltration of ESCA, regulation of glycolysis, regulation of ferroptosis, and ceRNA regulatory network.